2019
DOI: 10.1111/tid.13197
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment with isavuconazole of subcutaneous phaeohyphomycosis in a kidney transplant recipient

Abstract: Phaeohyphomycosis is a diverse group of uncommon mycotic infections caused bydematiaceous fungi which appears to be increasing in incidence, particularly in transplant recipients. Alternaria is the most frequent isolated genus. Subcutaneous, pulmonary and disseminated disease are the most common sites of Alternaria infection in solid organ transplant recipients. We report the first case, to our knowledge, of a kidney transplant recipient with Alternaria alternata subcutaneous infection who was successfully tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…21 Other advantages lie in its lower potential for drug–drug interactions and the lack of sulfobutyl-ether β-cyclodextrin. 15 Nevertheless, the available experience for the treatment of IMD in SOT recipients is scarce and restricted to case reports 22 and PK studies. 23,24 The only cohort study reported to date was performed in a single center where lung transplant (LuT) recipients with Aspergillus tracheobronchitis were overrepresented.…”
Section: Introductionmentioning
confidence: 99%
“…21 Other advantages lie in its lower potential for drug–drug interactions and the lack of sulfobutyl-ether β-cyclodextrin. 15 Nevertheless, the available experience for the treatment of IMD in SOT recipients is scarce and restricted to case reports 22 and PK studies. 23,24 The only cohort study reported to date was performed in a single center where lung transplant (LuT) recipients with Aspergillus tracheobronchitis were overrepresented.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, we reviewed 228 published reports. We identified and included 149 reports on 201 cases of dematiaceous fungal infections in SOT recipients 21–169 . The majority (134/149; 90%) of included reports scored ≥ 2 of three possible points on our bias assessment (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…However, PSZ tablets, which are widely used and unlikely to result in underexposure, may not justify routine TDM. 168,169,234,235,236,[238][239][240][241][244][245][246] Blood Trough 261,262,268,[281][282][283][284]314,315,320,323,327,330,331,333,340 Concentrations Targets 341,344,347,350,352,353,355,[358][359][360][361] and TDM Indications 364,522,[526][527][528][529][530][531][532][533][534][535][536]…”
Section: Discussionmentioning
confidence: 99%
“…2.2 (tablet) 533,534 2.5 234,245,366,[530][531][532]540,542 25-50 534,539 4-5 537 Documented exposure in CNS infection 2-5.8 69,535,536 3.6 236,[238][239][240][241]536 Concentration target ranges are, indicative; multidisciplinary approaches facilitate the real-life personalization of management, addressing one clinical condition in one patient at a given time. TDM access is of growing recognized interest, depending on disease severity, but cost and availability limit its use worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation